Discriminating progressive supranuclear palsy from Parkinson's disease using wearable technology and machine learning - De Vos, M; Prince, J; Buchanan, T; FitzGerald, JJ; Antoniades, CA (Elsevier, 2020)
Background Progressive supranuclear palsy (PSP), a neurodegenerative conditions may be difficult to discriminate clinically from idiopathic Parkinson’s disease (PD). It is critical that we are able to do this accurately and as early as possible in order that future disease modifying therapies for PSP may be deployed at a stage when they are likely to have maximal benefit. Analysis of gait and related tasks is one possible means of discrimination.